Students’ Ability in Using “To Be” at First Grade of SMP Sintuwu Maroso Poso - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2019)
The aims of this research to find the first students of SMP Sintuwu Maroso Poso ability in using “to be”.The problem formulation is: “What is the first year student’s at SMP Sintuwu Maroso Poso ability in using “tobe”. The method in this research is descriptive qualitative. Source of this research Students’ first semester at SMP Sintuwu Maroso Poso consist of 24 students. The result of this research finding shows: The ability of the SMP Sintuwu Maroso Poso using “to be” in English sentences was be categorized “poor”. It can be seen that the ability of the first year students of SMP Sintuwu Maroso Poso using to be in English sentences was very less